Unveiling the intricacies of protein-protein interactions and membrane fouling: Exploring hetero-protein complex formation in binary mixtures - Mapiour, Majak; Abdelrasoul, Amira (Biomedical engineering advances, 2024)
•Hetero-protein complexes formed in a mixture may either mitigate or worsen fouling.•In a mixture, fouling is contingent on proteins’ properties and respective concentrations.•Lysozyme and albumin serve as model proteins for studying fouling in binary mixtures.•Integrating DLVO, hydrodynamics, and spatial effects can improve a model's prediction. In practical applications, protein fouling studies often face limitations due to their reliance on single-protein feed experiments. It is crucial to acknowledge that interprotein interactions can significantly differ from intraprotein interactions, leading to variations in adsorption and membrane fouling behaviors. In this review, we delve into the dynamics of adsorption and membrane fouling, with a specific focus on single and binary solutions of Bovine Serum Albumin (BSA) and Lysozyme (LYZ) at or near physiological pH. These two proteins differ in terms of size, charge, and conformational stability, allowing for comparisons between small and large proteins, positively and negatively charged proteins, as well as rigid and flexible proteins. To gain further insights, we compare the findings from LYZ in single and binary solutions with those of alpha lactalbumin (α-LA), which, despite having opposite charges, shares a similar size with LYZ. The formation of BSA-LYZ heteroprotein complexes may introduce unique fouling trends in binary solutions compared to single solutions. This interplay can either enhance, reduce, or leave fouling unaffected. While studies employing the Extended DLVO (Derjaguin, Landau, Vervey, and Overbeek) theory to predict fouling in protein mixtures are limited, preliminary investigations using DLVO show promise. This approach has the potential to extend to binary and multi-protein feeds, providing valuable insights into the dynamics of fouling behavior in complex protein solutions. Considering that BSA is often used as a surrogate for Human Serum Albumin (HSA), the findings of this endeavor hold particular significance. HSA ranks the most abundant plasma proteins and, therefore, represents a crucial subject in numerous protein-related studies. [Display omitted]